Emotional variation in professional female basketball players during international competitions - Correia, R. F.; Haddad, C. R. R.; Augusto, J. B.; Fernandes, P. T. (International Journal of Sports Science, 2016)
There is vast interest by coaches on the correlates between athletic performance and athletes` emotional answers and adaptations to training and competition stimuli. This study had the objective of assessing emotional variation in the athletes composing the Brazilian Adult Female National Basketball Team during different periods of training in a four-month span using the Recovery-Stress Questionnaire for Athletes and the Profile of Mood States Questionnaire. Results showed that the athletes suffered no emotional variations during the different phases of physical training for the competitions in question. The possibility that these athletes engage in emotional coping mechanisms optimally during these training periods can explain these results. We believe that these results contribute to the investigations on efficient coaching practices for appraisal and management of athlete`s emotions and performance enhancement.